Implementation of Extracurricular Activities in Developing Students' Social Skills in Elementary Schools - Sofyan Iskandar; Primanita Sholihah Rosmana; Adela Agnia; Rayi Safitri; Tegar Selaras Gustavisiana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article uses a literature review method that looks for theoretical references related to the cases and problems found. The application of extracurricular activities in developing students' social skills in elementary schools is an important topic in the world of education. Extracurriculars provide opportunities for students to learn outside of an academic environment, which can help them develop the social skills necessary to interact with others. In the elementary school context, the implementation of extracurricular activities can help students build the ability to work together, communicate, leadership and tolerate differences. Through active participation in extracurricular activities such as scouts, choir, or sports, students can learn to work in teams, appreciate diversity, and increase their self-confidence. Therefore, the implementation of extracurricular activities in elementary schools has a significant role in shaping students' social skills for a better future.